Zakłady opieki zdrowotnej w czasach PRL (dygresja do monografii) - Durbajło-Mrowiec, Małgorzata; Ćwiąkała-Małys, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
After the Second World War, at the time of totalitarian government in Poland, the health care of Polish people was taken care of by the socialist authorities, obviously in a planned and centralized manner. However, the need of citizens for medical assistance was outside the plan. A network of social health care institutions and the Minster of Health was entrusted with most of the duties from this field of the socialist economic plan. Standardisation of employment and payment was introduced. The aim of this article is to present the rules of health care system functioning in a totalitarian country under the control of the society and to examine if the capacity of the new system was sufficient enough to meet the needs of the society and whether social resources were rationally allocated, according to the system’s assumptions. The article complements the research that was published in the monograph by Anna Ćwiąkała-Małys Anna, Małgorzata Durbajło-Mrowiec, Paweł Łagowski; Diagnostyka efektywności wykorzystania zasobów lecznictwa szpitalnego. The research was conducted with the usage of qualitative, comparative and praxeological method.
Keywords: health care system; financing of health care institutions; hospitals; budget